Geotecnology applied to management of public spaces: an analysis of the squares in the city Montes Claros - MG - Quintino, Camila Fabianne Barbosa; Tupinambá, Maria Levimar Viana; Leite, Marcos Esdras (Revista Cerrados, 2010)
The city as a concentration of wealth, suffers severe environmental problems, such as the presence of sewage and industrial effluents polluting rivers, lakes and aquifers, causing damage to fauna and flora. To try to alleviate the consequences caused primarily by greenhouse gas emissions in urban environments, man, devoted some areas that, besides serving as scavenging of pollutant gases, the presence of vegetation, serve as recreation areas. The parks and green areas, including them, the squares, have different functions that positively affect the human being beneficial to their lives, and beautify the living environment. The situations shown above occur in the city of Montes Claros where you can note that there is the presence of parks and green areas. But it is also possible to realize that in this city, are found several issues relating directly to environmental issues, especially the non-conservation of natural environments. Given the current environmental situation of the city of Montes Claros, in which there is an intensification of environmental problems due to population growth and the consequent expansion of built area, this study aimed to understand the distribution and conservation of urban plazas in Montes Claros, through the use of Geographic information technologies. But for this goal to be reached was necessary to think a methodological approach that regards the application of Geographic information technologies monitoring of the squares of Montes Claros. In this research, it was evident that the use of geographic information technologies served as support for a quick response on the issue of urban environment.